Automated User Experience Tool Development for Mobile Application - Ashraf Mousa Saleh , Anas Bassam Al-Badareen , Odai Enaizan (International Journal of Advanced Science and Technology, 2020)
UX evaluation has a significant importance for any interactive application. UX of mobile applications is very significant and there are some of automated tools available for evaluating such applications particularly for Android and iOS. Automated UX evaluation provides a number of strengths and overcomes the limitations of its non-automated (supervised) counterpart. Automated UX evaluation is regarded as unexplored field, especially when it is adopted for UX of large mobile application. The study was conducted by reviewing scientific papers that are related to user experience evaluation (UXEMs) to identify the most common UX attributes. Automated UX tool will be used to measure the metric of effectiveness, efficiency and satisfaction. In this study, the researcher used both subjective (UX Questionnaire) and objective measurements (Automated logging of effectiveness and efficiency) to satisfy study objectives. The study was conducted in Jordan as field study within Annual LogiCom Technology Forum (LTF); Twenty three participants used the Android phones that were made available by the researcher to carry out the tasks without any further adjustment of settings. Each test session was logged using automated UX tool. This paper presents an automated user experience tool to monitor user interaction for mobile applications. In this paper discusses the results and findings of automated UX tool for mobile applications.